METODE PELAKSANAAN PEKERJAAN RIGID PAVEMENT (STUDI KASUS: LAJUR KE – 3 JALAN TOL CIKOPO – PALIMANAN KM 87+350 - KM 98+275) - Sumantri, Vena Nuri; Rijaluddin, Arief (SEMINAR TEKNOLOGI MAJALENGKA (STIMA), 2025)
The Third Lane Widening Project from KM 87+350 to KM 98+275 of the Cikopo–Palimanan Toll Road, 2024 Package 1 has the primary objective of reducing traffic congestion caused by the high volume of vehicles on the Cikopo–Palimanan Toll Road by increasing the road capacity. This project is owned by PT. Lintas Marga Sedaya, supervised by the consulting firm PT. Indec Internusa, and executed by the contractor PT. Pembangunan Perumahan (Persero) Tbk. The project uses composite pavement, a combination of rigid pavement (concrete pavement) and flexible pavement (asphalt pavement). This report outlines the stages of rigid pavement work, including mobilization, preparation, and execution phases. Rigid pavement, or concrete pavement, is a type of pavement made of concrete with reinforcement such as tie bars and dowels, using concrete with a strength of fs’ 45. The report also includes the resources required based on the execution method.